Friend or Foe? Biomechanics and Its Key Role in Paediatric Orthopaedics - Jaap J. Tolk; Pieter Bas De Witte (MDPI AG, 2024)
Biomechanics play a key role in the development, progression and treatment of musculoskeletal disease in children [...]